2018
DOI: 10.1007/s11033-018-4260-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene–gene interactions of the Wnt/β-catenin signaling pathway in knee osteoarthritis

Abstract: This study was designed to investigate whether genetic polymorphisms of the Wnt/β-catenin signaling pathway and its interactions are involved in the development of knee osteoarthritis (KOA). Patients with KOA (n = 131) and healthy individuals (n = 190) with different ancestry from two Mexican populations (Mexico City and Guadalajara City) were analyzed. Twenty-five SNPs from thirteen genes (WISP1, DKK1, SOST, FRZB, LRP1, LRP4, LRP5, LRP6, GSKB, ADAMTS5, GDF5, FMN2 and COL11A1) involved in the Wnt/β-catenin sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Consistent with the literature, this research found that silence of HOTAIR inhibited inflammation response and oxidative stress in oxidized low-density lipoprotein-treated human macrophages by climbing miR-330-5p [25]. The Wnt/β-catenin pathway occupies a vital part in the regulation, proliferation, differentiation and cellular death processes [13]. This also accorded with the earlier observations, which made it clear that the Wnt/β-catenin pathway could be activated in IL-1β-induced chondrocytes [22].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the literature, this research found that silence of HOTAIR inhibited inflammation response and oxidative stress in oxidized low-density lipoprotein-treated human macrophages by climbing miR-330-5p [25]. The Wnt/β-catenin pathway occupies a vital part in the regulation, proliferation, differentiation and cellular death processes [13]. This also accorded with the earlier observations, which made it clear that the Wnt/β-catenin pathway could be activated in IL-1β-induced chondrocytes [22].…”
Section: Discussionsupporting
confidence: 88%
“…Wnt/β-catenin signaling takes a central part in liver tumor-initiating cells selfrenewal, and its activation is under accurate regulation [12]. As reported, the Wnt pathway is an necessary mechanism in the cartilage development and bone remodeling, and Wnt/β-catenin pathway is involved in knee OA pathogenesis [13]. The Wnt/β-catenin signaling pathway in an activated condition has been conveyed to be a cause for escalated β-catenin levels in articular cartilage and could further result in cartilage changes in OA at the early stage [14].…”
Section: Introductionmentioning
confidence: 92%
“…Numerous signaling pathways are involved in the process of OA, including bone morphogenetic proteins (8), Indian hedgehog (9), hypoxia-induced and Wnt signaling pathways (10,11). As an important component of the Wnt signaling pathway, β-catenin is activated by Wnt family proteins and participates in the pathological process of KOA (12). Previous studies have also demonstrated that the Wnt signaling pathway is involved in the homeostasis and degradation of the cartilage matrix by regulating the expression of anabolic or catabolic genes, such as increased expression of MMP-2, MMP-3, MMP-9, MMP-13, AdAMTS4 and AdAMTS5, which promote the degradation of the extracellular matrix and trigger KOA (13).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a great number of miRs, such as miR‐34a, miR‐27b, miR‐146a, and miR‐140, have been reported to be connected with OA pathogenesis 9 . Meanwhile, a study has suggestedthat gene‐gene interactions in the Wnt/β‐catenin signaling pathway plays a part in the etiology of knee OA 20 . Therefore, this study was to investigate how miR‐106 mediated Wnt3a/β‐catenin signaling pathway in the regulation of proliferation, differentiation, and apoptosis of chondrocytes in OA mice.…”
Section: Discussionmentioning
confidence: 99%